Characteristics of immunologic markers in pediatric acute lymphoblastic leukemia with genetic mutation at National Institute of Hematology and Blood Transfusion from 2016 to 2018 - Hong, Hoang Thi; Lan, Mai; Tung, Nguyen Quang; Van, Nguyen Trieu; Khanh, Bach Quoc (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.